2013
DOI: 10.1159/000350017
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Function in Preterm Infants Undergoing Patent Ductus Arteriosus Ligation

Abstract: Background: Targeted milrinone treatment for low left ventricular output (LVO) reduces the incidence of acute cardiorespiratory instability following ligation of patent ductus arteriosus (PDA) in preterm infants. Despite this, some infants continue to experience postoperative deterioration. Adrenal insufficiency related to prematurity has been postulated as a possible mechanism. Objectives: To describe adrenal function in premature infants undergoing PDA ligation and to investigate its association with pre- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 19 publications
(29 reference statements)
0
22
2
Order By: Relevance
“…Prior studies have noted that myocardial performance appears to be impaired (decreased LVO, decreased SF, and increased MPI) following PDA ligation (5, 6, 8, 9). Our findings are consistent with the prior reports, and support the hypothesis that impaired myocardial performance may contribute to the development of postoperative hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have noted that myocardial performance appears to be impaired (decreased LVO, decreased SF, and increased MPI) following PDA ligation (5, 6, 8, 9). Our findings are consistent with the prior reports, and support the hypothesis that impaired myocardial performance may contribute to the development of postoperative hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of dopamine and dobutamine could be used. Milrinone was not used to treat post-ligation hypotension (however, at one study site (7 infants), a milrinone infusion was started shortly after ligation as part of an institutional protocol designed to prevent postoperative hypotension (8, 9). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of hypothalamic-pituitary-adrenal function in very preterm infants is important as immaturity of the hypothalamic-pituitary-adrenal axis can lead to inadequate adrenal function in the face of acute illness [1,2] and corticosteroid therapy may influence adrenal function. For the purpose of cortisol measurement in preterm infants, easily available and workable methods are needed, ideally not inducing pain and stress to this vulnerable population [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies have not identified differences in the surgical, anesthetic, or intraoperative fluid management among the infants who develop postoperative hypotension (1, 4). Indices of impaired myocardial performance are often observed prior to the development of hypotension (58), and prophylactic administration of milrinone, begun shortly after the surgery, appears to reduce the incidence of postoperative cardiorespiratory instability. However, some infants continue to develop post-ligation hypotension despite early treatment of low ventricular output with milrinone (7, 8).…”
mentioning
confidence: 99%